Urinary Incontinence and Alzheimer’s Disease: Insights From Patients and Preclinical Models - Bartolone, Sarah N.; Sharma, Prasun; Chancellor, Michael B.; Lamb, Laura E. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease effects a large percentage of elderly dementia patients and is diagnosed on the basis of amyloid plaques and neurofibrillary tangles present in the brain. Urinary incontinence is often found in the elderly populations and multiple studies have shown that it is more common in Alzheimer’s disease patients than those with normal cognitive function. However, the link between increased urinary incontinence and Alzheimer’s disease is still unclear. Amyloid plaques and neurofibrillary tangles present in micturition centers of the brain could cause a loss of signal to the bladder, resulting in the inability to properly void. Additionally, as Alzheimer’s disease progresses, patients become less likely to recognize the need or understand the appropriate time and place to void. There are several treatments for urinary incontinence targeting the muscarinic and β3 adrenergic receptors, which are present in the bladder and the brain. While these treatments may aid in urinary incontinence, they often have effects on the brain with cognitive impairment side-effects. Acetylcholine esterase inhibitors are often used in treatment of Alzheimer’s disease and directly oppose effects of anti-muscarinics used for urinary incontinence, making urinary incontinence management in Alzheimer’s disease patients difficult. There are currently over 200 pre-clinical models of Alzheimer’s disease, however little research has been done on voiding disfunction in these models. There is preliminary data suggesting these models have similar voiding behavior to Alzheimer’s disease patients but much more research is needed to understand the link between urinary incontinence and Alzheimer’s disease and discover better treatment options for managing both simultaneously.